Unfinished business: terminated cancer trials and the relevance of treatment intent, sponsors and intervention types - Bürgy, Daniel; Riedel, Julian; Ehmann, Michael; Grilli, Maurizio; Hofheinz, Ralf-Dieter (International journal of cancer, 2021)
To report on the association of trial sponsors with intervention type, treatment intent, recruitment success and reasons to terminate cancer trials. The ClinicalTrials database was searched for interventional phase 3 cancer trials (01/2006-05/2017). Non-cancer studies and ongoing studies were excluded, permanently suspended studies were counted as terminated. Trials were stratified according to sponsors (industry/non-industry), intervention type, setting (curative/palliative) and intent of intervention (curative/symptom-control/life-extending). We identified 345 terminated trials and 1137 completed studies as a control group. The frequency of premature termination did not differ significantly between sponsors. Time to termination was shorter but recruitment per month prior to termination was higher in industry-sponsored studies (7.0 v. 2.2 patients/month; p < 0.001). Drug interventions were more common in industry-sponsored, all other interventions in non-industry-sponsored settings (p < 0.001). Life-extending palliative interventions occurred more frequently, symptom-control interventions in a curative setting less frequently in industry-sponsored trials (both p < 0.001). Intervention, setting, and intent were not associated with termination in industry-sponsored trials. In non-industry-sponsored trials, the frequency of drug interventions and life-extending (non-curative) interventions were increased in terminated trials (both p < 0.05); symptom-control interventions in curative settings occurred more frequently in completed studies. Industry-sponsored trials were more often terminated due to toxicity/inefficacy while lack of accrual occurred more frequently in non-industry-sponsored trials (p < 0.01). Interventions, treatment setting/intent and reasons for termination differed between sponsor type. In non-industry-sponsored trials, drug interventions and life-extending (non-curative) interventions were associated with premature termination and symptom-control interventions (curative setting) were associated with trial completion.
First published: 12 October 2020
Gesehen am 121.04.2021